Time taken for publishing articles in C-rated algerian magazines (El-Wahat Journal for Research and Studies, 2025)
This study’s purpose is to identify the length of time taken to publish articles in Algerian magazines on a sample of 72 scientific magazines according to decision n° 442 of 22 April 2021, which establishes the list of national scientific magazines of the category "C". This study concluded that the average length of articles’ publication in class C magazines is 8 months and 9 days, and the study even concluded that 40 magazines publish, 55.55% in short duration, 26 magazines publish, 36.11% in long duration and 6 magazines publish, in an average period, 8.33%. Although the length of time required to publish articles in magazines does not vary depending on the nature of the publication (quarterly, semi-annual, annual, once in two years).Keywords: time, Algerian magazines, scientific publication, scientific articles, class "C" magazines.